Critical thinking and creativity in STEAM-based collaborative learning on renewable energy issues - Ellianawati, Ellianawati; Subali, Bambang; Putra, Bayu Ramadhani; Wahyuni, Siti; Dwijananti, Pratiwi; Adhi, Mohamad Aryono; Yusof, Mohammad Mubarrak Mohd (Journal of Education and Learning (EduLearn), 2025)
Renewable energy is a global concern and should be incorporated into education to raise awareness among younger generations, including in physics education. Educators have made various efforts to raise awareness of the importance of pursuing renewable energy. A breakthrough sought in this research is to incorporate collaborative learning into the science-technology-engineering-art-mathematics (STEAM) approach. Integrating STEAM into collaborative learning can simultaneously develop critical and creative thinking skills by exploring local resources to become renewable energy sources. The research involved 36 high school students who met the criteria for having a smartphone and accessing a reliable internet connection. These conditions are designed to facilitate students' producing essays and posters exploring renewable energy sources in their local area. The research design employs a one-group pretest-posttest approach to assess the effectiveness of this STEAM-based collaborative learning process. The data collected from tests that have undergone t-tests and N-gain analysis, triangulated with observation data and questionnaires, illustrates the progress made in improving students' critical and creative thinking abilities. In conclusion, the implementation of STEAM-based collaborative learning demonstrates the highest level of achievement in creative thinking. It enables the production of innovative mini-projects that critically analyze local resources available for national energy sources.